Mrs. Lilly is silly! - Gutman, Dan (My weirder school ;, 2011)
On Career Day at Ella Mentry School, local reporter Mrs. Lilly helps A.J. and his fellow third-graders start a school newspaper, but their efforts have unexpected, and terrible, consequences.